2011
DOI: 10.1007/s00167-011-1585-y
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic muscle strength and knee function associated with double femoral pin fixation and fixation with interference screw in anterior cruciate ligament reconstruction

Abstract: The significant muscle strength outcome of the interference screw group found in this study gives initial evidence that this fixation technique is useful for athletes that may need accelerated rehabilitation. Early return to sports ability signaled by isokinetic muscle strength is of clinical relevance as it is one of the main goals for athletes' rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…Seventy-five remaining studies were reviewed in full text and 36 of these studies were excluded: 15 studies evaluated strength at more than 24 months following ACLR, 8 studies evaluated knee flexors only, 9 evaluated knee extensors only, 1 study repeated data used in a previous study, 1 study evaluated strength lying down and 2 studies evaluated isometric strength only. A final yield of 39 studies3 6–9 21 23 29 37–67 were included in this systematic review as presented in the flow chart (figure 1). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seventy-five remaining studies were reviewed in full text and 36 of these studies were excluded: 15 studies evaluated strength at more than 24 months following ACLR, 8 studies evaluated knee flexors only, 9 evaluated knee extensors only, 1 study repeated data used in a previous study, 1 study evaluated strength lying down and 2 studies evaluated isometric strength only. A final yield of 39 studies3 6–9 21 23 29 37–67 were included in this systematic review as presented in the flow chart (figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Seven were classified as good,43 45–47 53 55 66 26 as fair3 5–9 21 23 37–39 41 42 44 48–50 52 54 56 60–67 and 6 as poor 29 40 51 57–59. Thirty studies did not include all important adverse events that could have an effect on the intervention reported (criterion 8),5–7 9 21 23 29 38–40 42–52 54 56 57 59 60 63 64–67 23 studies did not adequately describe the source population and how they were recruited (criterion 11 and 12),3 5 6 8 21 37–40 42 44 48–52 54 57–60 64 65 24 studies did not describe if the source population was recruited in the same time period (criterion 22),3 8 9 23 29 37–42 44 48–52 54–58 63 64 66 and 29 studies did not report sample size calculation (criterion 27) 3 6–8 21 23 29 38–44 49–53 56–61 63–67. Other criterion, such as criterion 22 and 23, were not commonly fulfilled due to most studies not being randomised, while criterion 14 and 15 were not commonly reported due to lack of blinding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations